Sleep disturbances and depression are bidirectionally associated among college student athletes across COVID-19 pandemic exposure classes. (May 2023) - Petrie, Kyla A.; Messman, Brett A.; Slavish, Danica C.; Moore, E. Whitney G.; Petrie, Trent A.
Abstract: College athletes may be vulnerable to sleep disturbances and depression during the COVID-19 pandemic as a result of large shifts in social and athletic obligations. In a national sample of college athletes, we examined the associations between sleep disturbances and depression across two timepoints, using COVID-19 exposure as a moderator. Data were collected from 2098 NCAA Division I, II, and III college athletes during two timepoints, from April 10 to May 23, and from August 4 to September 15, 2020. First, a latent class analysis was conducted with five indicators of levels of COVID-19 exposure to determine different exposure profiles. Second, to examine the directionality of associations between sleep disturbance and depression, a cross-lagged panel model was added to the latent class membership structural equation model; this allowed for testing of moderation by COVID exposure class membership. Four highly homogeneous, well-separated classes of COVID-19 exposure were enumerated: Low Exposure (57%); Quarantine Only (21%); High Other, Low Self Exposure (14%); and High Exposure (8%). COVID-19 exposure class membership did not significantly moderate associations between sleep disturbances and depression. However, student athletes significantly differed in T2 depression by their COVID-19 exposure class membership. Depression and sleep disturbances were positively correlated at both timepoints ( r T1 = 0.39; r T2 = 0.30). Additionally, cross-lagged associations were found such that T2 depression was associated with T1 sleep disturbances ( β = 0.14) and vice versa ( β = 0.11). These cross-lagged associations were not significantly affected by athletes' level of COVID-19 exposure during the beginning of the pandemic. Highlights: 4 distinct classes of college student-athletes' COVID exposure experiences emerged. Depression levels in August 2020 differed by COVID exposure classes. Sleep disturbances and depression were positively correlated at both timepoints. Sleep disturbances and depression predicted each other across time. The bidirectional sleep-depression link was not moderated by COVID classes.